Enhancing Students’ Reading Interest by Developing Augmented Reality-Based Storybooks - Jannah, Wirda Jannatul; Melliofatria, Melliofatria; Corrina , Fatti (Journal of Educational Sciences, 2025)
This study aims to increase students' interest in reading by developing augmented reality (AR)-based storybooks. This study is a development study using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The difference between this storybook and others is that it uses Augmented Reality technology, and students create their own stories based on readings that interest them, as well as design the story images using the Canva application. This research was conducted on second-semester students majoring in Information Systems at Pasir Pengaraian University. The development instruments used were media expert validation sheets, material expert validation sheets, and user response questionnaires. The results of the first validator’s validation were a score of 50, with a percentage of 80% in the “Suitable” category from 12 statements. Meanwhile, the second validator obtained a score of 49, with a percentage of 81% in the “Very Suitable” category from 7 statements. Furthermore, from the user response questionnaire, a score of 97% was obtained, with a category of “Very Suitable” from 11 statements, involving 10 students as users. Based on these results, it can be concluded that the augmented reality (AR)-based picture storybook media is declared very suitable for use as a literacy learning medium.